1996
DOI: 10.1002/(sici)1097-0142(19960115)77:2<301::aid-cncr12>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Body mass and breast cancer: Relationship between method of detection and stage of disease

Abstract: Greater body mass was associated with nonlocalized breast cancer; however, this association was restricted to women who detected their own cancer. No association was found between BMI and stage of disease among cases detected by either mammography or CBE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 33 publications
6
42
1
Order By: Relevance
“…Findings from this case -control study provide support for an association between obesity and later stage at diagnosis, as it has been reported in most previous studies, mostly case-series (Daniell, 1988;Ingram et al, 1989;Verreault et al, 1989;Reeves et al, 1996;Jones et al, 1997;Hall et al, 1999;Cui et al, 2002), with a few exceptions (Donegan et al, 1978;Howson et al, 1986). In addition, consideration of all tumour characteristics simultaneously, suggested that obesity is primarily associated with larger tumour size rather than nodal status, particularly among postmenopausal women.…”
Section: Discussionsupporting
confidence: 88%
“…Findings from this case -control study provide support for an association between obesity and later stage at diagnosis, as it has been reported in most previous studies, mostly case-series (Daniell, 1988;Ingram et al, 1989;Verreault et al, 1989;Reeves et al, 1996;Jones et al, 1997;Hall et al, 1999;Cui et al, 2002), with a few exceptions (Donegan et al, 1978;Howson et al, 1986). In addition, consideration of all tumour characteristics simultaneously, suggested that obesity is primarily associated with larger tumour size rather than nodal status, particularly among postmenopausal women.…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis is supported by several studies that show a positive relationship between breast size and stage of breast cancer. 11,18,28,30 Second, obesity may be associated with a more advanced stage at diagnosis because of an underlying endocrinologic abnormality related to tumor progression. [43][44][45][46] Some studies suggest that locally increased estrogen levels promote tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies reported an association between increasing body mass index and advanced stage (Ingram et al, 1989;Hunter et al, 1993;Reeves et al, 1996) it is not clear why obese women seem to wait longer to present their breast cancer symptoms to a doctor. The results from our multivariable analyses indicate that the association between body mass index and patient delay is not explained by differences in health behaviour (as measured in our study), social class or education.…”
Section: Clinicalmentioning
confidence: 99%